A Systematic Review of Cardiorespiratory Fitness Tests Used in Dance. Issue 1 (March 2023) - Tiemens, Annemiek; van Rijn, Rogier M.; Koes, Bart W.; Stubbe, Janine H.
Dancers need adequate cardiorespiratory fitness (CRF) levels in order to cope with the demands of dance classes and choreographies. Screening and monitoring of CRF is advised. The aim of this systematic review was to provide an overview of tests used to assess CRF in dancers and to examine the measurement properties of these tests. A literature search was performed in three online databases (PubMed, EMBASE, and SPORTDiscus) up until August 16, 2021. Study inclusion criteria were: 1. a CRF test was used; 2. participants were ballet, contemporary or modern, or jazz dancers; and 3. English full-text peer-reviewed article. General study information, participant information, CRF test used, and study outcome were extracted. If available, measurement property data were extracted (i.e., test reliability, validity, responsiveness, and interpretability). Of the 48 articles included in the review, most used a maximal treadmill test (n = 22) or the multistage Dance Specific Aerobic Fitness test (DAFT; n = 11). Out of the 48 included studies, only six examined the measurement properties of CRF tests: Aerobic Power Index (API), Ballet-specific Aerobic Fitness Test (B-DAFT), DAFT, High-Intensity Dance Performance Fitness Test (HIDT), Seifert Assessment of Functional Capactiy for Dancers (SAFD), and the 3-minute step test. Good test-retest reliability was found for the B-DAFT, DAFT, HIDT, and SAFD. Criterion validity was determined for the VO2peak of the API, the 3-MST, HIDT, and SAFD. For HRpeak, criterion validity was studied for the 3-MST, HIDT, and SAFD. While different CRF tests are being used in descriptive and experimental research within dance populations, the body of research supporting the measurement properties of such tests is very small. As many studies have methodological flaws (e.g., small participant numbers or no statistical analysis for validity or reliability), additional good quality research is required to re-examine and complement current measurement property results of the API, B-DAFT, DAFT, HIDT, SAFD, and 3-MST.